Big Data Predictive Analytics and Performance: The Role of Transformational Leadership - et. al., Collins Ngu Nji, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of Big Data and Predictive Analytics (BDPA) have been overemphasized in recent years. However previous studies have been so focused on the developed and emerging market economies. The present research investigates this concept within the settings of a developing market economy. Also, the influence of transformational leadership (TL) in the adoption of BDPA as well as its moderation role between BDPA-Operational Performance (OP) nexus hasn’t been raised in prior studies. To address this, this study examines the combined effects of Mimetic Pressures (MP) and the Firm’s Human Skills (HS) as well as TL in the adoption of BDPA. The present study also examines the impact of TL on OP and its moderating role on the BDPA-OP nexus. Using a pre-tested questionnaire, the research hypothesis was tested on 145 surveys. The results of the empirical study indicate that MP has a positive but insignificant effect on the building and selection of HS and independently the adoption of BDPA is positively and significantly been influenced by both MP and HS. Likewise, BDPA has a positive and significant impact on OP. TL has a positive but insignificant effect in the adoption of BDPA and a negative and insignificant effect on OP. Also, the moderating effect of TL in the BDPA-OP nexus was found to be positive and seemingly significant.